El De Iudaica Arbore (1517) de Étienne Chenu y los conversos españoles en Tolosa y el Languedoc - María José Vega (Atalaya)
This article studies a text printed in Toulouse in 1517, the De arbore Iudaica, a work of fiction with theological, political and polemical implications which contains as well some allusions to current affairs in Toulouse. Its composition responds to different ends: the pointing out of the enemies of the Faith, warnings about the evils brought about by those that practice heresy and a desire to promote its extirpation from France. This treatise, beyond its intrinsic value, merits attention because of the elements that it brings to light as regards a possible Spanish reading public in Toulouse at the beginning of the Modern period.